Topography and Nonlinear Optical Properties of Thin Films Containing Iodide-Based Hybrid Perovskites - Agnieszka Marjanowska; Houda El Karout; Dominique Guichaoua; Bouchta Sahraoui; Przemysław Płóciennik; Anna Zawadzka (Nanomaterials, 2023)
This article covers selected properties of organic–inorganic thin films of hybrid perovskites with the summary formulas CH3NH3MI3, where M = Pb, Cd, Ge, Sn, Zn. The paper discusses not only the history, general structure, applications of perovskites and the basics of the theory of nonlinear optics, but also the results of experimental research on their structural, spectroscopic, and nonlinear optical properties. The samples used in all presented studies were prepared in the physical vapor deposition process by using co-deposition from two independent thermal sources containing the organic and inorganic parts of individual perovskites. Ultimately, thin layers with a thickness of the order of nanometers were obtained on glass and crystalline substrates. Their structural properties were characterized by atomic force microscopy imaging. Spectroscopic tests were used to confirm the tested films’ transmission quality and determine previously unknown physical parameters, such as the absorption coefficient and refractive index. Experimental results of the nonlinear optical properties were obtained by studying the second and third harmonic generation processes and using initial sample polarization in the so-called Corona poling process. The obtained experimental results allowed us to determine the second- and third-order nonlinear optical susceptibility of the tested materials.